2016
DOI: 10.1016/j.jvs.2016.04.043
|View full text |Cite
|
Sign up to set email alerts
|

Acute renal artery occlusion: Presentation, treatment, and outcome

Abstract: Most patients presenting with acute kidney infarction are managed conservatively. A subset of patients with complete occlusion of the renal artery undergo CDT with good angiographic results. The treated kidney is expected to decrease in size over time, and overall kidney function is expected to decrease compared with baseline. Deterioration in renal function appears to stabilize and does not continue over time. CDT for acute renal artery occlusion is a safe modality of therapy and should be attempted for the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
72
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 10 publications
(9 reference statements)
1
72
0
3
Order By: Relevance
“…However, ther e are some cases that renal function was recovered after renal artery occlusion for several days [4,7,8,23]. Maybe the collateral circulation which arises from lumber, suprarenal, and ureteral vessels plays a signifi cant role in the renal function preservation after prolonged ischemia time for these cases [23,24]. The left renal function of our patient was severely damaged, in spite of only 8 hours of symptom onset and combination use of multiple interventional techniques.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…However, ther e are some cases that renal function was recovered after renal artery occlusion for several days [4,7,8,23]. Maybe the collateral circulation which arises from lumber, suprarenal, and ureteral vessels plays a signifi cant role in the renal function preservation after prolonged ischemia time for these cases [23,24]. The left renal function of our patient was severely damaged, in spite of only 8 hours of symptom onset and combination use of multiple interventional techniques.…”
Section: Discussionmentioning
confidence: 65%
“…Once the warm ischemia time exceeds 2 hours, only 30% -50% of renal function can be recovered [21]. More than 90 min u tes of acute warm ischemia has been recommended as a cut point for the recovery of renal function [22].while it is well known that early diagnosis and treatment are essential to preserving renal function, it is controversial to adopt treatment measures after prolonged ischemia time [23]. However, ther e are some cases that renal function was recovered after renal artery occlusion for several days [4,7,8,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Percutaneous revascularization of acutely occluded RA becomes a new therapeutic option for the treatment of renal failure caused by ischemia of the kidneys [1][2][3][4][5][6]. Such an endovascular management is technically feasible and can restore diuresis even in severely compromised patients and after relatively long period of renal ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…1 There is no consensus treatment strategy for iRI, because previous studies have not reported long-term outcomes based on therapeutic intervention. 2 3 4 5 6 7 8 9 10 11 12 13 14 15 We sought to determine if anticoagulation or nonanticoagulation was associated with a higher incidence of recurrent arterial thrombosis, de novo venous thrombosis, bleeding event, or development of long-term hypertension, proteinuria, or chronic kidney disease (CKD).…”
Section: Introductionmentioning
confidence: 99%